2015
DOI: 10.1063/1.4921893
|View full text |Cite
|
Sign up to set email alerts
|

Strong thermal nonequilibrium in hypersonic CO and CH4 probed by CRDS

Abstract: A new experimental setup coupling a High Enthalpy Source (HES) reaching 2000 K to a cw-cavity ring-down spectrometer has been developed to investigate rotationally cold hot bands of polyatomic molecules in the [1.5, 1.7] μm region. The rotational and vibrational molecular degrees of freedom are strongly decoupled in the hypersonic expansion produced by the HES and probed by cavity ring-down spectroscopy. Carbon monoxide has been used as a first test molecule to validate the experimental approach. Its expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…In view of this, spectroscopic measurements are carried out for hypersonic jet of carbon monoxide and argon using cavity ring-down spectroscopy (CRDS). These studies are continuation of the earlier findings of Louviot et al [12] where as well double peak structure of absorption lines had been observed for carbon monoxide in CRDS based measurements. Therefore present investigations specifically deal with analysis of absorption line shapes for line of sight spectroscopic measurements.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…In view of this, spectroscopic measurements are carried out for hypersonic jet of carbon monoxide and argon using cavity ring-down spectroscopy (CRDS). These studies are continuation of the earlier findings of Louviot et al [12] where as well double peak structure of absorption lines had been observed for carbon monoxide in CRDS based measurements. Therefore present investigations specifically deal with analysis of absorption line shapes for line of sight spectroscopic measurements.…”
Section: Introductionsupporting
confidence: 91%
“…Experiments are carried out in an experimental facility having a High Enthalpy Source (HES) connected to a vacuum chamber [12,13]. In the present studies, carbon monoxide (Air Liquide, 99.998% purity) is used as the seeding gas (5% by mass) and argon (Air Liquide, 99.998% purity) as the carrier gas (95% by mass).…”
Section: Experimental and Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of new experimental techniques such as the High Enthalpy Source (HES), developed by R. Georges and coworkers, coupled to a high-resolution Fourier transform spectrometer (FTS) allows the recording of high temperature emission spectra of polyatomic molecules (C 2 H 2 and CH 4 ) [33,34,35] up to about 2000 K. Recently, a new experimental setup coupling the HES to a cw-cavity ring-down spectrometer has been developed by the same group to investigate rotationally cold hot bands of polyatomic molecules in the 1.5-1.7 µm region [36]. Hargreaves et al developed an original approach to produce emission-corrected FTIR transmittance spectra of hot gases such as methane [37] and ethane [38].…”
Section: Introductionmentioning
confidence: 99%
“…The latter set-up also uses cw-CRDS and the expansion is produced using a very large roots pumping system [265]. All experimental conditions are reported in [219].…”
Section: H 2 O-h 2 Omentioning
confidence: 99%